Pengembangan Kreativitas Melalui Seni Gerak dan Tari pada Anak Usia Dini di RA Hj Siti Syarifah - Hilda Zahra Lubis; Janatun Fadhilah; Nadia Chairy Batubara; Sapna Tanjung (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to examine the impact of dance movement art learning on the development of creativity, motor skills, and social-emotional wellbeing in preschool children (ages 4-6). The study employs a descriptive qualitative method with a subject group of 28 children from TK Harapan Bunda, Jakarta. Data was collected through participatory observation, interviews with teachers and parents, and documentation of the learning process over 6 months. The findings indicate that the implementation of dance movement art learning with a thematic approach and free movement exploration can: (1) enhance children's expressive ability and creativity in creating movement variations, (2) significantly develop both gross and fine motor skills, (3) improve teamwork skills and social spatial awareness, and (4) help children express emotions constructively. This research recommends the importance of integrating dance movement art into the early childhood education curriculum with an approach that emphasizes freedom of expression and creative exploration.